Specific detection of duck adeno-associated virus using a TaqMan-based real-time PCR assay - Chen, Shuyu; Chen, YuYi; Zhang, Mengyan; Zhang, Wenyu; Fu, Huanru; Huang, Yu; Cheng, Longfei; Wan, Chunhe (Frontiers in Veterinary Science, 2024)
Duck adeno-associated Virus (DAAV) is a novel pathogen that was recently discovered in ducks. To establish a molecular detection assay for DAAV for further epidemiological investigation and pathogenic mechanism. Here, we designed specific primers and probes according to the sequence characteristics of the newly discovered DAAV and then established a TaqMan real-time PCR method (TaqMan-qPCR) for the detection of DAAV. Our data showed that the established TaqMan-qPCR for detecting DAAV had high sensitivity, with the lowest detection limit of 29.1 copies/μL. No cross reaction was found with duck circovirus (DuCV), H9N2 subtype avian influenza virus (AIV), avian Tembusu virus (ATmV). duck hepatitis A virus 1 and 3 (DHAV-1 and DHAV-3), duck adenovirus A (DAdV-A), duck adenovirus 3 (DAdV-3), or duck enteritis virus (DEV). The repeatability was excellent, with the coefficients of variation of repeated intragroup and intergroup tests ranging from 0.12–0.21% and 0.62–1.42%, respectively. Seventy-eight clinical samples collected from diseased or deceased ducklings were tested. The results showed that the DAAV positive rate was 21.79%, and a triple infection (DAAV+MDPV+GPV) was found. These data provide technical support for further molecular epidemiological surveillance and pathogenic mechanism studies of DAAV infection.